Exploring parents' knowledge and attitudes towards the influenza vaccine in a rural community of Saudi Arabia - Hanan I. Alomran; Abdullah S. Al-Dosary; Fahad M. AlGhamdi; Ziyad M. Alshahrani; Nawaf S. Altayar (AOSIS, 2022)
Influenza is a highly transmissible respiratory virus. Public awareness about the nature of the disease and how to prevent it must be explored to effectively mitigate the adverse effects of the disease. This study aimed to assess the parents' knowledge and attitudes towards the influenza and the influenza vaccine in Al-Kharj Governate, Saudi Arabia. A cross-sectional study was performed, and an electronic questionnaire was distributed from December 2020 to the end of April 2021 to parents living in Al-Kharj, Saudi Arabia. Data were collected and analyzed using IBM SPSS version 21. The study had 510 participants, of which 75.1% were mothers. Overall knowledge about the influenza disease was found to be low in 68.6% of participants. In addition, 55.7% of respondents displayed an inadequate level of knowledge of the influenza vaccine. Almost 75% of parents had chosen not to vaccinate their children in the past and of those, only 35.9% were willing to vaccinate their child this year. The most common reason for parents choosing not to vaccinate their children was that they believed the child to be in good health. This demographic studied in Al-Kharj, Saudi Arabia did not demonstrate sufficient knowledge about the influenza disease and vaccine. Study participants were hesitant to vaccinate their children. This should prompt healthcare workers and the Ministry of Health to lead a broad awareness campaign on influenza vaccination that extends to both urban and rural areas.